2013
DOI: 10.1371/journal.pone.0077528
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Asian Chytrid Strain Infection in Threatened and Endemic Anurans of the Northern Western Ghats, India

Abstract: The Western Ghats of India harbors a rich diversity of amphibians with more than 77% species endemic to this region. At least 42% of the endemic species are threatened due to several anthropogenic stressors. However, information on amphibian diseases and their impacts on amphibian populations in this region are scarce. We report the occurrence of Batrachochytridium dendrobatidis (Bd), an epidermal aquatic fungal pathogen that causes chytridiomycosis in amphibians, from the Western Ghats. In the current study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 36 publications
(51 reference statements)
1
47
0
Order By: Relevance
“…Bd is widely distributed throughout Asia [67] and has been present in the region since at least 1911 [68], but no reports exist of disease-driven mortality or population declines [67]. Many distinct genotypes are being described from the regions, including Japan [69], Korea [70] and India [71] as well as Bsal [58]. The growing diversity of chytrid pathogens of amphibians from Asia suggests a likely site of origin for these pathogens.…”
Section: (B) Chytrid Present But Impacts On Amphibians Varied or Unkmentioning
confidence: 99%
“…Bd is widely distributed throughout Asia [67] and has been present in the region since at least 1911 [68], but no reports exist of disease-driven mortality or population declines [67]. Many distinct genotypes are being described from the regions, including Japan [69], Korea [70] and India [71] as well as Bsal [58]. The growing diversity of chytrid pathogens of amphibians from Asia suggests a likely site of origin for these pathogens.…”
Section: (B) Chytrid Present But Impacts On Amphibians Varied or Unkmentioning
confidence: 99%
“…nov. need verification. Based on the examination of vouchers, we suggest that the records of R. bombayensis from Tamhini (Dahanukar & Padhye 2005) and Taleghar (Dahanukar et al 2013), should be considered as R. ghatei sp. nov. tuberohumerus from Thoseghar by Padhye & Ghate (2012) should also be asigned to R. ghatei sp.…”
Section: Discussionmentioning
confidence: 98%
“…Pande et al (2013) have discussed threat of wind farms to avifauna wherein they discuss the windmill erection activity to be a measured threat to general diversity as well. Recently, Dahanukar et al (2013) reported the presence of chytrid fungal infection in morphologically identified R. bombayensis from Taleghar, which should be attributed to the R. ghatei sp. nov. based on the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Western Ghats is known as an amphibian hot spot. For the first time in 2011 "killer fungus" Batrachochytrium dendrobatidis which causes Chytridiomycosis in amphibians was reported from Western Ghats (Nair et al 2011), further its widespread occurrence in Western Ghats was reported in 2013 and 2015 (Dahanukar et al 2013;Molur et al 2015). Amphibian trade and introductions are prominent hypotheses for the spread of B. dendrobatidis in many parts of the world (Fisher & Garner 2007).…”
Section: Methodsmentioning
confidence: 99%